A new strategy for mitigation of the allergenic activity of ovomucoid in hen eggs and beta-lactoglobulin in cow milk. Issue 1 (2016) - Kido, Jun; Nishi, Natsuko; Misumi, Sachiko; Matsumoto, Tomoaki
No abstract available